(untitled) (Research, Society and Development, 2022)
Measles is an acute infectious disease of viral etiology that is common in children and can develop into severe complications. The objective of the current research is to analyze the prevalence of measles and to correlate this with the vaccination coverage for the disease, in the municipality of Marabá, State of Pará, from 2019 to 2020. A retrospective, descriptive epidemiological study with an analytical approach was conducted. Secondary data available from the Health Department of the municipality of Marabá and the Information System for Notifiable Diseases (SINAN) were used. A total of 113 measles cases were found in the municipality of Marabá between 2019 and 2020. There was a predominance of measles cases among children younger than one year and between 20 and 34 years old, the most frequent sex was male and the most frequent schooling was complete high school. As for vaccination coverage, a downward trend was observed between the years 2000 and 2020. Vaccination campaigns in the Municipality of Marabá should be intensified with specific strategies to reach the groups with the highest incidences of measles, with the objective of inhibiting the transmission of the virus.